Legitimacy threats and organizational responses : drivers leading to symbolic vs substantive actions - Pinto, Tomás da Fonseca Farinha Varela (2016)
In my dissertation I investigate the drivers leading organizations to respond symbolically versus substantially to legitimacy threats due to their (perceived) socially irresponsible behaviours. To do so, I conducted a qualitative research over ten Food & Beverage (F&B) companies subject to a legitimacy threat as a result of their misleading marketing practices. My findings suggest that it is possible to group these organizations in three distinct profiles: a) The Committed Actors, which solely engage in substantive actions; b) The Calculating Actors, whose first response concerns denial of responsibility followed by symbolic actions and c) The Compliant Actors, which first deny their responsibility and implement substantive actions at a later stage. On the basis of these findings, my work contributes to the literature by shedding light on the interplay between symbolic and substantive actions and by unveiling the internal and external organizational drivers shaping this interplay. My study also demonstrates to have some managerial implications because it shows the role of corporate social responsibility in organizations’ attempt to gain stakeholders’ support.